The effects of 5x5 exercises on a quality of life of university students, who use smartphones during long periods - Aysenur Tuncer; Tuba Maden; Tugba Badat; Deniz Kocamaz (Physical Education of Students, 2020)
Background and Study Aim. The present study investigated the effect of a 5x5 exercise program on sleep quality, fatigue, neck pain, head posture, daily walking, sitting, sleeping and smartphone usage time.